CM082 suppresses hypoxia-induced retinal neovascularization in larval zebrafish - Zhang, Jun-long; Fan, Ding-gang; Yin, Wu; Hu, Bing (Frontiers in Pharmacology, 2024)
Retinal neovascularization is a common feature of several ocular neovascular diseases, which are the leading cause of blindness in the world. Current treatments are administered through invasive intravitreal injections, leading to poor patient compliance, serious ocular complications and heavy economic burdens. Thus, an alternative less or non-invasive therapeutic strategy is in demand. Here, a non-invasive oral tyrosine kinase inhibitor, CM082, was evaluated in a retinal neovascularization model induced by hypoxia in zebrafish larvae. We found that CM082 effectively suppressed retinal neovascularization, rescued cell loss in the retinal ganglion cell layer, and rescued the visual function deficiency. Preliminary mechanistic study indicated that CM082 may work through inhibiting the expression of vegfr2. The findings demonstrated that CM082 possessed strong antiangiogenic effects and may serve as a potential treatment for angiogenesis in ocular neovascular diseases.